Identification of a novel plant-derived attractant for Acromyrmex lobicornis leaf-cutting ants - Alma, Andrea Marina (2019)
Leaf-cutting ants are considered major pests of agriculture and forestry in the Neotropics. Attractive toxic baits are the prevailing method for managing them. Thus, there is great interest in identifying attractants to incorporate into these baits. Moreover, leaf-cutting ants can avoid toxic baits by associating the attractant with the toxin. We evaluated attractiveness of heptyl butyrate, a volatile compound found in fresh apples and plums. We conducted field experiments with ten colonies of Acromyrmex lobicornis. First, we evaluated the behaviour of ants exposed to heptyl butyrate at 1% by surrounding resources. Then, we compared the attractiveness of heptyl butyrate and orange pulp, the most commonly used attractant. Finally, we evaluated whether heptyl butyrate increases the attractiveness of a carbohydrate resource at varying doses. Heptyl butyrate at 1% attracted 92% more ants than the control and that it was as attractive as orange pulp. Heptyl butyrate paired with sucrose at concentrations of 0.001 and 0.1% was more attractive than sucrose alone, but greater concentrations did not increase sucrose’s attractiveness. Therefore, heptyl butyrate could be added to toxic baits to manage A. lobicornis as it is as attractive as the most commonly used attractant and can be applied directly to the pellets.